Gambaran Tingkat Pengetahuan Wanita Usia Subur Tentang Gejala Fisik pada Masa Menopause di Wilayah Kerja Puskesmas Salewangeng Kabupaten Wajo - Resky Nuraini; Tetti Surianti; Eka Wulansari; Lisna Lisna (Journal Research of Nursing & Midwifery (JRNM), 2026)
Menopause is a natural physiological process in women characterized by the cessation of the menstrual cycle due to declining levels of estrogen and progesterone. Hormonal changes during menopause may cause various physical symptoms, including hot flashes, night sweats, sleep disturbances, joint pain, decreased bone density, and changes in the skin and hair, which may affect women's health and quality of life. Adequate knowledge of the physical symptoms of menopause is essential to enable women to recognize and prepare for the changes associated with this transition. This study aimed to describe women's level of knowledge regarding the physical symptoms experienced when entering menopause. This study employed a quantitative method with a cross-sectional design. The study sample consisted of 253 respondents selected using a total sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. The data were analyzed using univariate analysis and presented as frequency distributions and percentages. The results showed that the majority of respondents had a moderate level of knowledge (52.6%), while 29.3% had a low level of knowledge and only 18.2% demonstrated a good level of knowledge regarding the physical symptoms of menopause. In conclusion, most respondents had a moderate level of knowledge about the physical symptoms that may occur during menopause. However, a considerable proportion of respondents still had insufficient knowledge, indicating the need for continuous health education and counseling accompanied by regular evaluation to improve women's understanding of the physical changes and potential health impacts associated with menopause